Mosquito bite immunization with radiation-attenuated Plasmodium falciparum sporozoites: safety, tolerability, protective efficacy and humoral immunogenicity - Hickey, Bradley W.; Lumsden, Joanne M.; Reyes, Sharina; Sedegah, Martha; Hollingdale, Michael R.; Freilich, Daniel A.; Luke, Thomas C.; Charoenvit, Yupin; Goh, Lucy M.; Berzins, Mara P.; Bebris, Lolita; Sacci, John B.; et al. (Malaria journal, 2016)
In this phase 1 clinical trial, healthy adult, malaria-naïve subjects were immunized with radiation-attenuated Plasmodium falciparum sporozoites (PfRAS) by mosquito bite and then underwent controlled human malaria infection (CHMI). The PfRAS model for immunization against malaria had previously induced >90 % sterile protection against homologous CHMI. This study was to further explore the safety, tolerability and protective efficacy of the PfRAS model and to provide biological specimens to characterize protective immune responses and identify protective antigens in support of malaria vaccine development. Fifty-seven subjects were screened, 41 enrolled and 30 received at least one immunization. The true-immunized subjects received PfRAS via mosquito bite and the mock-immunized subjects received mosquito bites from irradiated uninfected mosquitoes. Sera and peripheral blood mononuclear cells (PBMCs) were collected before and after PfRAS immunizations. Immunization with PfRAS was generally safe and well tolerated, and repeated immunization via mosquito bite did not appear to increase the risk or severity of AEs. Local adverse events (AEs) of true-immunized and mock-immunized groups consisted of erythaema, papules, swelling, and induration and were consistent with reactions from mosquito bites seen in nature. Two subjects, one true- and one mock-immunized, developed large local reactions that completely resolved, were likely a result of mosquito salivary antigens, and were withdrawn from further participation as a safety precaution. Systemic AEs were generally rare and mild, consisting of headache, myalgia, nausea, and low-grade fevers. Two true-immunized subjects experienced fever, malaise, myalgia, nausea, and rigours approximately 16 h after immunization. These symptoms likely resulted from pre-formed antibodies interacting with mosquito salivary antigens. Ten subjects immunized with PfRAS underwent CHMI and five subjects (50 %) were sterilely protected and there was a significant delay to parasitaemia in the other five subjects. All ten subjects developed humoral immune responses to whole sporozoites and to the circumsporozoite protein prior to CHMI, although the differences between protected and non-protected subjects were not statistically significant for this small sample size. The protective efficacy of this clinical trial (50 %) was notably less than previously reported (>90 %). This may be related to differences in host genetics or the inherent variability in mosquito biting behavior and numbers of sporozoites injected. Differences in trial procedures, such as the use of leukapheresis prior to CHMI and of a longer interval between the final immunization and CHMI in these subjects compared to earlier trials, may also have reduced protective efficacy. This trial has been retrospectively registered at ISRCTN ID 17372582, May 31, 2016.